A novel tissue microarray instrumentation:The HT-1 tissue microarrayer - Jun Yang; Mingjuan Zhang; Baoshan Su; XiaoLi Chen; AnJing Kang (Wolters Kluwer Medknow Publications, 2012)
Background: Tissue microarray (TMA) is a novel and useful tool to efficiently analyze gene expression in histological tissues. Aim: Cost-efficient and easy to use automated tissue arrayers will provide a better instrumentation to generate TMAs. Thus, we designed and produced our tissue microarrayer to meet these needs. Materials and Methods: The HT-1 tissue microarrayer we designed and manufactured consists primarily of four parts, including an instrument to make array pores for the recipient paraffin blocks, a punch needle, an instrument for negative-pressure embedding, and a special manipulator. By using the HT-1, 14 different TMAs were made to accommodate 312 cases of tissues and TMA sections were tested by hematoxylin-eosin (H&E) staining, in situ hybridization, and immunohistochemistry. Results: Expand: Hematoxylin and eosin staining showed that the tissue cylinders were similar, even, and in order on the slides. Most importantly, the HT-1 microarrayer can make array pores in the recipient paraffin block with a single application in seconds. The HT-1 also contains a unique negative pressure system for embedding TMA blocks. In addition, HT-1 can make tissue cylinders with the same levels and depth for equally embedded and sectioning. Conclusions: The HT-1 tissue microarrayer is a device that is simple, economical and easy to use.